Mixed Finite Element Technologies - Carstensen, Carsten; Wriggers, Peter; SpringerLink (Online service) (Vienna : Springer Vienna, 2009)
Mixed finite element methods are a tool to solve complex engineering problems of different nature. This subject is treated in the volume from the engineering and the mathematical point. Different applications are considered which depict the value of mixed formulations in engineering on one side. On the other side the mathematical background is provided including proofs of convergence and stability of these methods and adequate solvers for mixed problems are discussed. This broad spectrum yields an indepth treatment of mixed methods from different perspectives.
Lectures on Adaptive Mixed Finite Element Methods -- Fast Solvers for Mixed Finite Element Methods -- Numerical Simulation of Charge Transport in Semiconductor Devices Using Mixed Finite Elements -- Numerical Simulation of Thermal Oxidation Process in Semiconductor Devices Using Mixed$1 (BHybrid Finite Elements -- Mixed Finite Element Methods - Theory and Discretization -- Stability of Some Finite Element Methods for Finite Elasticity Problems.s
Keywords: Engineering; Applied mathematics; Engineering mathematics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering; Appl.Mathematics/Computational Methods of Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Electronic books